2018
DOI: 10.1155/2018/5684150
|View full text |Cite
|
Sign up to set email alerts
|

Light Emission by Nanoporous GaN Produced by a Top-Down, Nonlithographical Nanopatterning

Abstract: Temperature-dependent photoluminescence (PL) spectroscopy is carried out to probe radiative recombination and related light emission processes in two-dimensional periodic close-packed nanopore arrays in gallium nitride (np-GaN). The arrays were produced by nonlithographic nanopatterning of wurtzite GaN followed by a dry etching. The results of Raman spectroscopy point to a small relaxation of the compressive stress of ~0.24 GPa in nanoporous vs. bulk GaN. At ~300 K, the PL emission is induced by excitons and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The dot marked as Position 1 (the yellow dot and spectrum) at the bottom of the stack corresponding to the pure GaN region and the peak near 372 nm is a characteristic CL peak for bulk GaN. [39,40] Figure 2d,e show the CL line-scan results along the yellow and red arrows directions indicated in Figure 2b, respectively. According to our CL measurement, it is found that the InGaN/AlGaN QWs mainly emit in the range of 510-538 nm (indicated by the green arrows in Figure 2c, corresponding to green light).…”
Section: Resultsmentioning
confidence: 99%
“…The dot marked as Position 1 (the yellow dot and spectrum) at the bottom of the stack corresponding to the pure GaN region and the peak near 372 nm is a characteristic CL peak for bulk GaN. [39,40] Figure 2d,e show the CL line-scan results along the yellow and red arrows directions indicated in Figure 2b, respectively. According to our CL measurement, it is found that the InGaN/AlGaN QWs mainly emit in the range of 510-538 nm (indicated by the green arrows in Figure 2c, corresponding to green light).…”
Section: Resultsmentioning
confidence: 99%